2022
DOI: 10.1109/access.2022.3212774
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Multiuser SWIPT Communications for 5G+

Abstract: Increasing number of devices connected to the networks, applications and demands of new generation wireless communications cause very high energy consumption resulting in large amount of carbon emission. Thus, energy harvesting solutions together with accomplishing information transmission are required for energy efficient communications of new wireless communications generations such as 5G and 6G (i.e., 5G+). As such, due to the promise of energy efficient green communications, simultaneous wireless informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 279 publications
0
10
0
Order By: Relevance
“…In [11], the authors showed that, for the fully digital beamforming case, the optimal solution to the semidefinite relaxation version of the power minimization problem expressed as ( 8) is also the optimal solution to problem (8). We extend the proof to the hybrid precoding case.…”
Section: B Proof Of Propositionmentioning
confidence: 78%
See 3 more Smart Citations
“…In [11], the authors showed that, for the fully digital beamforming case, the optimal solution to the semidefinite relaxation version of the power minimization problem expressed as ( 8) is also the optimal solution to problem (8). We extend the proof to the hybrid precoding case.…”
Section: B Proof Of Propositionmentioning
confidence: 78%
“…We assume that the multiplication between an m × p matrix and a p × n matrix has a time complexity of O(mpn), and the complexities of computing the inverse and determinant of an n × n matrix are both O(n 3 ). Referring to [34], the computation load of FullyDig, which solves problem (8) with the interior-point algorithm, is known as O(…”
Section: E Complexity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Energy consumption increasing not only increases the cost of implementing wireless communication systems but also it will be a severe challenge for the environment. Wireless energy harvesting technology is one of the ways to solve the energy consumption challenge [6]. In fact, wireless energy harvesting helps harvest wireless energy from natural and unnatural sources.…”
mentioning
confidence: 99%